Potential Effects of Silymarin and Its Flavonolignan Components in Patients with β-Thalassemia Major: A Comprehensive Review in 2015 - Hadi Darvishi Khezri; Ebrahim Salehifar; Mehrnoush Kosaryan; Aily Aliasgharian; Hossein Jalali; Arash Hadian Amree (Advances in Pharmacological Sciences)
Major β-thalassemia (β-TM) is one of the most common inherited hemolytic types of anemia which is caused as a result of absent or reduced synthesis of β-globin chains of hemoglobin. This defect results in red blood cells lysis and chronic anemia that can be treated by multiple blood transfusions and iron chelation therapy. Without iron chelation therapy, iron overload will cause lots of complications in patients. Antioxidant components play an important role in the treatment of the disease. Silymarin is an antioxidant flavonoid isolated from Silybum marianum plant. In the present study, we reviewed clinical and experimental studies investigating the use of silymarin prior to September 1, 2015, using PubMed, ISI Web of Knowledge, Science Direct, Scopus, Ovid, and Cochrane Library databases and we evaluated the potential effects of silymarin on controlling the complications induced by iron overload in patients with β-TM. Based on the results of the present study, we can conclude that silymarin may be useful as an adjuvant for improving multiple organ dysfunctions.